CLOUD COMPUTING ADOPTION IN SMES: AN EMPIRICAL STUDY USING PLS-SEM" - Laviza Asif Memon; Naeem Akbar Channar; Dr. Ali Raza Rang; Javed Ahmed Dahri (Spectrum of Engineering Sciences, 2025)
Cloud computing is game changing technology for these small and medium-sized enterprises (SMEs) as they can now avail cheap and scalable IT solutions. This study examines the relationship from perceived usefulness, security concern and cost efficiency to SMEs cloud adoption, and used organization readiness as the mediator in the process. Using a quantitative explanatory research design, data were collected through a 7-point Likert-type scale from a sample of 209information technology (IT) managers, system administrators, and decision-makers in SMEs of Karachi. A Structural Equation Modeling (SEM) was applied on the data using Smart PLS, which explored both direct and indirect relationships. It found that both perceived usefulness and cost efficiency had a significant impact on cloud adoption, while security concerns had a significant deterrent effect. Moreover, the finding demonstrated that organizational readiness has a significant mediating role about the relationships between the independent variables and cloud access. And the findings of the study can support the decision-makers in the SME sector, as well as policymakers with investment towards cloud technology sentiment, especially IT infrastructure improvements and more managerial involvement in cloud adoption.